Microvascular Response to the Roos Test Has Excellent Feasibility and Good Reliability in Patients With Suspected Thoracic Outlet Syndrome - Henni, Samir; Hersant, Jeanne; Ammi, Myriam; Mortaki, Fatima-Ezzahra; Picquet, Jean; Feuilloy, Mathieu; Abraham, Pierre (Frontiers in Physiology, 2019)
Background: Exercise oximetry allows for operator-independent recordings of microvascular blood flow impairments during exercise and can be used during upper arm provocative maneuvers. Objective: To study the test-retest reliability of upper-limb oximetry during the Roos test in patients with suspected thoracic outlet syndrome (TOS). Material and methods: Forty-two patients (28 men, 14 women; mean age: 40.8 years) were examined via transcutaneous oxygen pressure (TcpO2) recordings during two consecutive Roos tests in the standing position. The minimal decrease from rest of oxygen pressure (DROPmin) value was recorded after each maneuver performed on both arms. The area under the receiver operating characteristics (ROC) curve defined the DROPmin diagnostic performance in the presence of symptoms during the tests. The Mann-Whitney test was used to compare the DROPmin in symptomatic vs. asymptomatic arms. Test-retest reliability was analyzed from Bland-Altman representations. Results are mean+/-SD or Median [25-75 centile]. Results: The symptoms by history were different from the symptoms expressed during the Roos maneuvers in one-third of the patients. The DROPmin measurements were -19 [-36; -7] mmHg and -8 [-16; -5] mmHg in the symptomatic arms (n=108) and asymptomatic arms (n=60), respectively. With the presence of TOS observed on ultrasound imaging as an endpoint, the area under the ROC was 0.725±0.058, with an optimal cutoff point of -15 mmHg, which provided a 67% sensitivity and 78% specificity for the presence TOS via ultrasound. With the presence of symptoms during the test as an endpoint, the area under ROC was 0.698+/-0.04, with a cutoff point of -10 mmHg, which provided a 62% sensitivity and 66% specificity for the presence of pain in the ipsilateral arm during the test. The test-retest reliability of DROPmin proved to be good but not perfect, partly because of unreliability of the provocation maneuvers. Conclusion: This study is the first to investigate microvascular responses during the Roos maneuver in patients with suspected TOS. The presence of symptoms was significantly associated with ischemia. TcpO2 allows for the recording of both macrovascular and microvascular responses to the Roos test. The Roos maneuver should probably be performed at least twice in patients with suspected TOS.